Cores e seus significados no senso comum para apoiar a colaboração na aprendizagem via web : uma solução em forma de Padrões de Design Motivacionais - Dias, Ana Luiza (Universidade Federal de São Carlos, 2009)
Collaborative learning supported by computers increases due to the tendency schools have to get assumed to digital inclusion in curriculum and to explore this potential as an alternative complementary to the traditional teaching methodology. According to this new practice the individual skills are valued and contribute to build up learning, which belongs to the group. However, it can be seen that learning through computing environment is not always effective because it can generate lack of motivation, little involvement and collaboration as there are limitations in computational proposals, which must always be seen as complementary to face interaction. It is always difficult to engage apprentices in learning activities in order to motivate them both to persist in challenging tasks and to value education, generally. In order to minimize the inequality of socioeconomic conditions and provide solutions that can consider cultural values of each learner involved in a collaborative task, this work shows the formalization of a Motivational Design Proto-Pattern Set based on colors and their cultural meanings built in common sense of the Brazilian. This set aims to support educational solution design to Web, which promotes collaboration, since colors may highlight important points, facilitate content reading and consequently, increase the satisfaction of use of computer resources and engagement of apprentice in their learning. The common sense used comes from the knowledge base of the Open Mind Common Sense Brazil Project (OMCS-Br) (http://www.sensocomum.ufscar.br). In order to validate this work, a Web collaborative educational environment has been modified changed applying on one of the formalized proto-patterns, and the environment was used in Vivência-Anglo S.S. Educational School in Itapira/SP, a partner in the LIA in the study of computer applications for childhood education, where was developed a case study. The results have pointed out the potential of color as a stimulus to motivation and learning, as well as the interest between educators and apprentices on Web collaborative educational environments, breaking the learning traditional paradigm, now with the computer support.
Keywords: Interação homem-máquina; Padrões motivacionais; Motivação na educação; Senso comum; Cores; Emoções; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO